2020
DOI: 10.1002/jnr.24607
|View full text |Cite
|
Sign up to set email alerts
|

Profilin 1 knockdown prevents ischemic brain damage by promoting M2 microglial polarization associated with the RhoA/ROCK pathway

Abstract: Microglial polarization to the anti-inflammatory M2 phenotype is essential in resolving neuroinflammation, making it a promising therapeutic strategy for stroke intervention. The actin cytoskeleton is known to be important for the physiological functions of microglia, including migration and phagocytosis. Profilin 1 (PFN1), an actin-binding protein, is involved in the dynamic transformation and reorganization of actin. However, the role of PFN1 in microglial polarization and ischemia/reperfusion injury is uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 49 publications
(68 reference statements)
0
18
0
Order By: Relevance
“…This process could disturb orchestrated actin polymerization at the membrane and thus decrease phagocytosis. In addition to direct effects on the actin cytoskeleton, PFN1 knockdown has also been reported to result in anti-inflammatory changes 57 . Indeed, we observed transcriptional changes in immune-related genes and AD risk genes upon PFN1 overexpression in iTF-Microglia (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process could disturb orchestrated actin polymerization at the membrane and thus decrease phagocytosis. In addition to direct effects on the actin cytoskeleton, PFN1 knockdown has also been reported to result in anti-inflammatory changes 57 . Indeed, we observed transcriptional changes in immune-related genes and AD risk genes upon PFN1 overexpression in iTF-Microglia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that PFN1 overexpression disrupts the actin cytoskeleton in iTF-Microglia with higher levels of F-actin. Recently, a study has shown that PFN1 is also involved in microglia activation, since knockdown of PFN1 inhibited M1 proinflammatory microglial polarization and promoted anti-inflammatory M2 microglia polarization after oxygen and glucose deprivation 61 . Introducing the ALS-associated mutations in the PFN1 gene in iPSCs will shed light on the impact of these specific mutations on the function of different relevant cell types, such as iPSC-derived neurons and microglia.…”
Section: Discussionmentioning
confidence: 99%
“…), transforming growth factor β (TGF-β), brain-derived neurotrophic factor (BDNF) (Boche et al, 2013;Hu et al, 2015), and help restore the homeostasis of the central nervous system (Gogoleva et al, 2019). Therefore, promoting microglia conversion to M2 type is considered a therapeutic strategy for cerebral ischemic injury (Lu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They were incubated at 37 °C in a humidified 5% carbon dioxide atmosphere, with medium changed every 2 days. To mimic cerebral I/R injury in vitro , cells were exposed to OGD/R as previously reported [ 25 ]. Briefly, the medium was replaced with D-glucose-free DMEM (Corning), and incubated at 37 °C in a hypoxic incubator (94% nitrogen and 5% carbon dioxide) for 2 h to simulate OGD damage.…”
Section: Methodsmentioning
confidence: 99%